Representation of tropical deep convection in atmospheric models – Part 2: Tracer transport - C. R. Hoyle (Atmospheric Chemistry and Physics, 2011)
The tropical transport processes of 14 different models or model versions were compared, within the framework of the SCOUT-O3 (Stratospheric-Climate Links with Emphasis on the Upper Troposphere and Lower Stratosphere) project. The tested models range from the regional to the global scale, and include numerical weather prediction (NWP), chemical transport, and chemistry-climate models. Idealised tracers were used in order to prevent the model's chemistry schemes from influencing the results substantially, so that the effects of modelled transport could be isolated. We find large differences in the vertical transport of very short-lived tracers (with a lifetime of 6 h) within the tropical troposphere. Peak convective outflow altitudes range from around 300 hPa to almost 100 hPa among the different models, and the upper tropospheric tracer mixing ratios differ by up to an order of magnitude. The timing of convective events is found to be different between the models, even among those which source their forcing data from the same NWP model (ECMWF). The differences are less pronounced for longer lived tracers, however they could have implications for modelling the halogen burden of the lowermost stratosphere through transport of species such as bromoform, or short-lived hydrocarbons into the lowermost stratosphere. The modelled tracer profiles are strongly influenced by the convective transport parameterisations, and different boundary layer mixing parameterisations also have a large impact on the modelled tracer profiles. Preferential locations for rapid transport from the surface into the upper troposphere are similar in all models, and are mostly concentrated over the western Pacific, the Maritime Continent and the Indian Ocean. In contrast, models do not indicate that upward transport is highest over western Africa.